A review of the effect of Coenzyme Q10 in patients with polycystic ovary syndrome - Shahad Badr; Zeina Althanoon (University of Mosul, 2021)
Background: Women with polycystic ovary syndrome are usually suffering from many metabolic disturbances as insulin resistance, so the use of Co enzyme Q10 in those patients improve metabolic changes and insulin resistance resulting in better ovulation.Mitochondrial dysfunction in the eggs is related to reduction in the oxidative phosphorylation which leads to lower ATP production by mitochondria, also results in deprived reproductive performance, including poor oocyte quality, lessened ovarian store, abnormal conception and unbalanced embryo development.Objective: The aim of this review is to observe the effects of co enzyme Q10 in PCOS patients by emphasizing many studies that showing the effect of CoQ10 on the metabolic parameters such as (Fasting serum glucose, HbA1c%, total cholesterol, LDL, HDL and triglyceride level).This article suggested that CoQ10 therapy possess beneficial effect in improving the clinical parameters of PCOS patients including HbA1c%, fasting serum glucose and lipid profile parameters.